A garantia de direitos das comunidades tradicionais indígenas frente às políticas públicas de desenvolvimento sustentável: Guaíra - PR - Oliveira, Claudia Regina de (2016)
This work is a result of a Master s Degree research carried out during the years of 2015/2016 in the Graduation Program of Rural Sustainable Development (Programa de Pós-Graduação em Desenvolvimento Rural Sustentável) of Western Parana State University (Universidade Estadual do Oeste do Paraná), in the investigation area of Rural Sustainable Development. It analyzes the rights of indigenous peoples and traditional Guaraní communities in Guaira, through the observation of the varied forms of organization of these groups, the social services provided to them e and the confrontation with the violations and vulnerability of fundamental rights, mediated by public policies and the process of sustainable development. According to the National Commission of Sustainable Development (Comissão Nacional de Desenvolvimento Sustentável), the pledge for legal acknowledgment of the so-called traditional communities , demanded by different social movements and assured in the Brazilian Constitution/88, increased as of 2012, through a series of governmental measures that have intensified its attainment. The groups analyzed here are: Tekoha Porã and Tekoha Marangatu, located in Guaira, in western Parana. As per the IGBE website (2007), until the second half of the XVI century, the area situated on the left bank of Parana river, which was Paraguayan territory, as well as all the area that constitutes the state of Paraná, was exclusively inhabited by savages, distributed in numerous tribes, and they were, until then, the only and rightful owners of the land. Their unquestionable domination lasted for many years. In the roll of the indigenous population registered in the Siasi/Funasa 2007, there are 38 people registered in Guaíra, resulting in R$ 38.000,00 of ICMS Ecológico (environmental tax revenue) (BRASIL. Ministério da Saúde, 2007). Taking into account the lack of information and fragmented knowledge about the indigenous population in Guaira, this research is justified by the objective of gathering information on the profile of this traditional population to provide the relevant authorities with data that can lead to concrete actions of support and in the attainment of national public policies for indigenous peoples concerning local sustainable development. This work is formed by five chapters. The fieldwork methodologies are interviews and visits to these communities, and it is authorized by FUNAI (process no. 08620.021130/2015-85), with a statement of merit from CNPq and by the ethics committee